Mycobacterium avium subsp. paratuberculosis (MAP) in Goat Milk in the Semiarid Region of the Brazilian Northeast - Molecular Characterization - Roberto, João Paulo de Lacerda; Limeira, Clécio Henrique; Rodrigues Soares, Rafael; Araújo Júnior, João Pessoa; Malossi, Camila Dantas; Ullmann, Leila Sabrina; Silva, Maria Luana Cristiny Rodrigues; Higino, Severino Silvano dos Santos; Azevedo, Sérgio Santos; Alves, Clebert José (Acta Scientiae Veterinariae, 2022)
Background: Goat farming has been on the rise in Brazil in recent years. Overall, 93% of the national herd is concentrated in the Northeast, with the state of Paraíba being the largest goat milk producer in the country. Considering Mycobacterium avium subsp. paratuberculosis (MAP) as a sanitary issue for the development of animal farming with risks for human health and that is a notifiable disease, this research was structured with the objective of confirming the presence and performing a molecular characterization of MAP in goat milk destined for processing plants in the semiarid region of the Brazilian Northeast. Materials, Methods & Results: Samples from 179 production units and 5 collective bulk tanks and 4 samples of pasteurized goat milk were analyzed through Real-time polymerase chain reaction (qPCR). Genetic material (DNA) for MAP was found in the goat milk sample from 1 production unit (1/179). From this positive sample, 9 lactating goats were identified in the original property, 7 of which showed MAP DNA in milk samples (77.77%). The characterization of the nucleotide sequence detected in the positive sample has 99% identity with KJ173784. Discussion: One sample (1/179), from the production units, had MAP genetic material (DNA) detected using the molecular test. Samples from these production units represent the milk from all lactating goats from each producer. Therefore, it was possible to identify from which farm the samples originated, allowing individual animals to then be tested, with milk samples collected from 9 goats and MAP DNA detected in 7 of them (77.77%) via PCR. Control and/or prevention programs need this type of surveillance in reason that it allows the tracking of possible foci from milk samples collected from dairy products or cooling stations. The use of PCR to detect MAP foci via goat milk is thus advantageous because samples are obtained in a non-invasive manner, with faster results when compared to the culture technique. The low detection via PCR in goat milk may be related to factors such as the small amount of MAP eliminated and the intermittent excretion in asymptomatic animals, as also false-positive samples. Samples from the collective bulk tanks was negative. It is possible that the combination of milk from all the properties diluted the amount of MAP. This suggests that the sensitivity of the PCR can be improved if the samples are obtained from the pooled milk from the same property. In some regions of Brazil, for example, showed the frequency of Zona da Mata region of the state of Minas Gerais, Brazil, found 1.94% of positive samples (9/464) and 9.76% (4/41) of properties with at least 1 positive sample for MAP. Different results to what were found in the semiarid region of Paraíba, where climate and production characteristics are different. Goats are susceptible to 3 strains: type “S” (Sheep), “Bison type” and type “C” (Cattle). Previous contact with this species may explain the similarity between the strain found in goat milk and those detected from bovine samples. This must also be taken into consideration during diagnosis and upon implementation of control measures for paratuberculosis in goats. Mycobacterium avium subsp. paratuberculosis was recorded for the first time in goat milk in the semiarid region, which may reveal a potential biological risk to humans and suggests the need for active surveillance of the agent. Keywords: paratuberculosis, Johne’s disease, caprine, milk, PCR.